Defining myopia using refractive error and uncorrected logMAR visual acuity >0.3 from 1334 Singapore school children ages 7–9 years. Issue 3 (17th February 2006) - Luo, H-D; Gazzard, G; Liang, Y; Shankar, A; Tan, D TH; Saw, S-M
Abstract : Aim: To determine the association of spherical equivalent (SE) with low uncorrected visual acuity (VA) along with a proposed definition for myopia using logMAR VA >0.3 as the criteria. Methods: 1334 Chinese schoolchildren (mean age 7.8; range 7–9 years) were enrolled in the study after those who had hyperopia ⩾+2.00 dioptres (D) and astigmatism > = −2.00D were excluded. Uncorrected logMAR VA was measured for both eyes. Cycloplegia autorefraction was achieved by the instillation of three drops of 1% cyclopentolate 5 minutes apart. The average of five successful consecutive refraction and keratometry readings were obtained with calibrated Canon RK5 autokeratorefractometers by well trained optometry students, at least 30 minutes after the instillation of the third drop of cyclopentolate. SE cut-off points (−0.25D, −0.5D, −0.75D, −1.0D) were evaluated. Results: Using different SE cut-off points, the myopia prevalence rates of this sample of schoolchildren varied from 45.8% (SE at least −0.25 D) to 30.7% (SE at least −1.0 D). The cut-off point of ⩾−0.75 D had a sensitivity and specificity of 91.8% (95% CI, 89.2 to 94.4) and 93.7% (95% CI, 92.1 to 95.3), respectively, to predict low vision defined as uncorrected logMAR VA > 0.3 (either eye). The next best cut-off point of −0.5D had a higher sensitivity (93.3%), but lower specificity (87.9%). Conclusions: The cut-off points of −0.75D and −0.5D in SE refraction are appropriate for the prediction of uncorrected logMAR VA worse than 0.3, which is the criterion for the US common state adult driver licensing standard.